Logistics education for business management students: a learningdoing and service-learning approach - Cano, Jose Alejandro; Ayala, Carlos (Opción, 2020)
This article develops a teaching methodology in logistics for students of business administrationprograms to solve real problems in companies and integrate the knowledge acquired in logisticsmanagement courses. The methodology integrates project management tools with the supportof MSExcel and promotes the elaboration of managerial reports according to the requirementsof working environments. The methodology generates high satisfaction in the students, to theextent that it allows them to know in depth the logistic system of a company, identifiesopportunities for improvement and proposes solutions based on technical and economicaspects. Likewise, the methodology allows the students to have contact with the directives of areal company and supports the improvement of logistics processes based on qualitative andquantitative information  AbtracSe desarrolla una metodología de enseñanza en logística para estudiantes de programas de administración de empresas para resolver problemas reales en empresas e integrar los conocimientos adquiridos en cursos de gestión logística. La metodología integra herramientas de gestión de proyectos con el soporte de MSExcel. Promueve la elaboración de informes gerenciales conforme con los requisitos de los entornos de trabajo. La metodología genera una gran satisfacción en los estudiantes, en la medida en que les permite conocer en profundidad el sistema logístico de una empresa, identifica oportunidades de mejora y propone soluciones basadas en aspectos técnicos y económicos. Asimismo, permite a los estudiantes tener contacto con las directivas de una empresa real y apoya la mejora de los procesos logísticos basados en información cualitativa y cuantitativa.